Bounce Resonance Scattering of Radiation Belt Energetic Electrons by Extremely Low‐Frequency Chorus Waves. Issue 22 (18th November 2021) - Guo, Deyu; Xiang, Zheng; Ni, Binbin; Cao, Xing; Fu, Song; Zhou, Ruoxian; Gu, Xudong; Yi, Juan; Guo, Yingjie; Jiao, Luhuai
Abstract: Bounce‐resonant diffusion coefficients of radiation belt energetic electrons induced by extremely low‐frequency (ELF) chorus waves are comprehensively evaluated using Van Allen Probes observations on December 22, 2014. ELF chorus waves can efficiently scatter 85° < α eq < 89° electrons with bounce resonance pitch angle scattering rates above 10 −4 /s and energy scattering rates above 10 −7 /s. By comparing diffusion coefficients due to bounce resonance with those due to cyclotron and Landau resonances, we found that bounce resonance diffusion rates have slight energy dependence for >100 keV electrons while Landau‐resonant scattering rates decrease significantly in the MeV energy range. These findings suggest that bounce resonances by ELF chorus waves have potentially significant contributions to the dynamics of energetic electrons and should be considered in the further modeling of Earth's radiation belts. Plain Language Summary: In geospace environment, various plasma wave modes can interact with electrons by cyclotron, Landau, and bounce resonances. One important wave mode called chorus generally has frequencies above 0.1 f ce ( f ce is the electron gyro‐frequency). However, recent studies reported <0.1 f ce chorus waves, which is called extremely low‐frequency (ELF) chorus waves. The wave‐particle interactions by ELF chorus waves due to cyclotron resonances have been well‐studied while the bounce‐resonant interaction has not been investigated. In this study, using Van Allen Probes satellites observations on December 22, 2014, we evaluate the bounce‐resonant effect on radiation belt energetic electrons induced by ELF chorus waves and compare it with the other two resonance types. These results suggest that ELF chorus waves can efficiently lead to the dynamics of electrons by bounce resonance. The effect of bounce resonance has slight energy dependence and can be offset by Landau resonance. The bounce resonance effect by ELF chorus waves should be considered in the modeling of Earth's radiation belts. Key Points: Electron pitch angle and energy diffusion due to bounce resonance with extremely low‐frequency (ELF) chorus are evaluated in detail Bounce resonance by ELF chorus can scatter electrons at high equatorial pitch angles with the Dαα above 10 −4 /s and the DEE above 10 −7 /s Different from chorus‐driven cyclotron and Landau resonances, the bounce resonance by ELF chorus has slight energy dependence